The Association of Age, Parity, and History of Cesarean Section with the Occurrence of Placenta Accreta Spectrum (Pas) at H. Adam Malik Hospital in Medan 2020-2022 - Siagian, Beby Febyola; Pasaribu, Hotma Partogi; Kusumawati, R. Lia; Daulay, Rini Savitri (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Background: Maternal mortality rate (MMR) is an indicator of the quality of midwifery services in a country. Postpartum hemorrhage is a serious life-threatening complication and the main cause of maternal death especially that caused by placenta accreta spectrum (PAS). This study aims to determine the relationship between age, parity, and history of cesarean section on the incidence of PAS at H. Adam Malik Hospital Medan in 2020-2022.Method: This study was an analytic-observational study with a cross-sectional design. The data used came from the medical records, including information about the population of mothers who gave birth, maternal age at delivery, parity, and previous history of cesarean section. Statistical analysis used univariate and bivariate chi-square tests.Result: The study subjects were 84 people selected by simple random sampling method. The results of the univariate analysis showed the highest frequency of age >32 years, parity 3-4 times, and a history of cesarean section â‰¥ 2. The results of bivariate analysis showed a significant relationship between age and the incidence of PAS (p=0.016), parity and the incidence of PAS (p<0.001), and a history of cesarean section and the incidence of PAS (p=0.004).Conclusion: There is a relationship between age, parity, and history of cesarean section with the incidence of PAS at H. Adam Malik Hospital Medan in 2020-2022.